Is the Anti-Atlas of Morocco still uplifting?. (April 2022) - Lanari, R.; Reitano, R.; Giachetta, E.; Pazzaglia, F.J.; Clementucci, R.; Faccenna, C.; Fellin, M.G.
Abstract: Topographic elevation of orogenic belts in the results of several processes and contributions occurring at different temporal and spatial scales, from short-to long-term and from the surface up to the mantle. Disentangle surface evolution on key areas may then encode for deeper ongoing processes. In this concern, the Anti Atlas of Morocco is a prominent mountain belt with moderate relief and with a long deformation history not recorded during the Cenozoic. The modern topography of the Anti-Atlas is resulted from late Miocene uplift driven by mantle processes. In this study, we address the question if mantle processes are still affecting the topography of the Anti-Atlas by providing new clues on the late Miocene-Quaternary uplift history of the north-western margin of the mountain belt. We analyze and compare the river long profiles and related morphometric features of channels draining the Souss Basin of the Anti-Atlas in western Morocco with analog and numeric similar scenarios. We find that the steepness of the rivers, the χ, ksn, slope and local relief show limited values. Moreover, the channels are characterized by Quaternary fluvial conglomerates lying at high elevation. The projection of the non-re-equilibrated river profile runs below the lower part of the channel. We explore the mechanism that could produce this feature by both numerical and analog models. The analogue and numerical long river profiles from modeling show similar morphometric features compared to the natural case when the uplift rate is diminished or set to zero. We speculate that in the Anti Atlas, uplift may have waned over Quaternary time leading to a spatial change in the critical point of sedimentation, triggering valley infilling at high elevation, and in turn a slow burying of the Anti-Atlas. Highlights: The Anti-Atlas and High Atlas show remarkable difference in topographic metrics. Analogue-Numerical models show similar features compared to the Anti-Atlas. Uplift waning changes the point of sedimentation, triggering the valley infilling.